ISLAM DAN POLITIK PEMERINTAHAN (Pemikiran Politik Muhammad Husein Haikal) - Kesuma, Arsyad Sobby (Universitas Islam Negeri Raden Intan Lampung, 2013)
Discussing themes or concepts of Islamic government system seems to be an endles activity as a great number of books written by muslim intellectuals from time to time continously appear. the present day. This paper tries to explore ideas and political thought of one Muslim intellectual , Muhammad Husayn Haykal. After a thorough scrutinization to his works, this study finds out that his conception of political thought was based on the Oneness of Allah (Tauhidiyah). In addition, he also identified three basic principles of humanism upon which Islamic state should be based, namely : the principles of human brotherhood, of human equality, and of human freedom. Haykal also asserted that the form of constitutional state is preferable as compared to others .